Laser Tattoo (Tattooing) Removal with Responsibility of The Doctor: A Case Report - Yolaçan, Ebru; Dağ Oğlakcıoğlu, Gülşah; Cantürk, Gürol (The Bulletin of Legal Medicine, 2018)
Tattoo (tattooing) is a practice that continued from ancient times to modern-day. It represents a belief for communities, a social class or the identity. Tattoo is applied to human body in different patterns and colors. Some of the mare temporary while others are permanent. The ink injected into the dermis layer ensures that tattoo is permanent. Tattooing has gained prevalence among young people in recent years. Associated with prevalent, later, depending on the increase of those who want to be removed tattoo, scientists have searched for different treatments on tattoo removal methods. Some of these methods are destructive techniques such as dermabrasion, cryosurgery, electrosurgery and surgical excision. Since they have a lot of side effects, laser technology has advanced in recent years. The most common method used today for tattoo removal is the Q- switched laser method. A few clinics are aimed at disintegrating the tattoo painting by interfering with...